Alterations in Kumite techniques and the effects on score rates following the 2013 International Judo Federation rule revision - Ito, K.; Hirose, N.; Maekawa, N.; Tamura, M.; Nakamura, M. (Archives of Budo, 2015)
Background and Study Aim: Significant changes in kumite tactics could be expected following the 2013 International Judo Federation rule revision, which mandated that competitors initiate sparring immediately at match outset. The research contained in this paper focused on the specific areas of kumite that were likely to be affected by this rule revision. Material and Methods: In total, 396 men`s contests were selected from All Japan Judo Federation DVDs. Throws resulting in scores were identified and the preceding kumite was analyzed. Chi-square tests were performed to determine variations in the number of scored throws between the 2012 and 2013 contests based on predetermined criteria and comparisons of kumite efficacy were made using the resulting score ratios. Results: Re-gripping resulted in a higher score rate in aiyotsu, kenkayotsu and the total of both stances. (P=0.022, P=0.033, P=0.002; respectively). The score rate increased when both hands were used for throwing in the aiyotsu stance and the total of both stances (P=0.017, P=0.002; respectively). The score rate increased in cases where the competitor grabbed their opponents in places other than the collar or sleeve with both hands or in a place other than the collar or sleeve with one hand and the collar or sleeve with the other hand when the competitors sparred in the kenkayotsu stance and in the total of both stances combined (P=0.007, P=0.010, respectively). Conclusions: Re-gripping the opponent and targeting locations other than the collar and sleeves for grabbing might facilitate scoring. This should be considered by trainers and competitors when preparing for competitions.